Reflections on Christopher Alexander’s principles as a basis for good practices in urban analysis - Calvetti, Fernando dos Santos (Seven Editora, 2024)
This article reflects on the relevance of Christopher Alexander’s discourse for current urban analysis, largely based on the computational power of modeling urban configuration and dynamics. Configurational analysis of cities is an essential approach to understanding and improving the way urban spaces develop and function. Among the infinite possibilities of analysis of this complex and constantly changing object, the use of mathematical instruments and models that seek to simulate urban relations and dynamics has gained more and more traction in academia, especially in the forms of configurational studies and urban syntax. In the meantime, Christopher Alexander is recognized for his innovative contributions to the understanding of urban form and its relationship with the flows that occur in the city. Alexander’s approach is also fundamental for configurational analysis, as it offers a robust theoretical framework to understand how urban elements connect and interact in a functional and harmonious way. It emphasizes the importance of an urban structure that is adaptable, organic, and able to evolve over time to better serve the communities that live in it. This holistic and humanized vision of urbanism is crucial to address the contemporary challenges of cities. DOI:https://doi.org/10.56238/sevened2024.018-058